2014
DOI: 10.11113/jt.v68.3024
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of Cellulase and Xylanase for Cross-Linked Enzyme Aggregates

Abstract: Cross-linked enzyme aggregate is a promising strategy among other enzyme immobilization technologies such as solid matrix linking and gel entrapping. Despite of having the advantage of being reused, cross-linked enzyme aggregate (CLEA) also offers greater stability during operation and storage. Preparation of CLEA involves two steps which are precipitation and cross-linking of the enzymes. The purpose of this study is to find the best precipitant for cross-linked enzyme aggregate of cellulase and xylanase. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, it can be stated that the precipitation depends on the type of enzyme and that parameter optimization is required in the synthesis of CLEAs for each enzyme separately. Sulaiman and co-workers reported that the activity for precipitated cellulase using ammonium sulfate retained 60.1% of the original activity ( Sulaiman et al, 2014 ). For instance, in our study, residual activity of precipitated cellulase was higher (79%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be stated that the precipitation depends on the type of enzyme and that parameter optimization is required in the synthesis of CLEAs for each enzyme separately. Sulaiman and co-workers reported that the activity for precipitated cellulase using ammonium sulfate retained 60.1% of the original activity ( Sulaiman et al, 2014 ). For instance, in our study, residual activity of precipitated cellulase was higher (79%).…”
Section: Resultsmentioning
confidence: 99%
“…This immobilization technique is usually carrier-free and involves assemblage of enzymes to form a three-dimensional structure ( Luna et al, 2016 ). CLEAs synthesis is a promising strategy among other enzyme immobilization techniques, which also offers greater stability during operation and storage ( Sulaiman et al, 2014 ) towards denaturation by heat, organic solvents, and autoproteolysis and are stable towards leaching in aqueous media ( Sheldon, 2011 ). A high content of free amino groups, especially on the surface of an enzyme, is crucial to create strong intermolecular bonds between the free amino and polymers or oligomers resulting from the aldol condensation of glutaraldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, SSF for the production of cellulases offers numerous advantages such as high productivity, relatively high concentrations of the products and less effluent generation (Acharya and Chaudhary 2012) as well as, higher yields and product stability (Singhania et al 2009). It seems that different precipitants constructed a more stable structure for the enzyme and keep the enzyme in its origin conformational even after immobilization (Sulaiman et al 2014). In consistence with our results, Kalyani et al (2015) reported that the activity of partially purified enzyme by ammonium sulphate increased than that of the crude enzyme.…”
Section: The Influence Of Storage Periods On the Activity Of Cmcase Immobilized In Ca-alginatementioning
confidence: 99%
“…Aer 10 min incubation, the reaction was stopped by the addition of 1 mL DNS reagent. 18 The reaction terminated at zero times was used as control tubes. The absorbance (OD) of the reducing sugar was measured at 540 nm.…”
Section: Enzyme Assaysmentioning
confidence: 99%